O Axé nas roupas: indumentária e memórias negras no candomblé angola do Redandá - Pereira, Hanayrá Negreiros de Oliveira (2018)
The present research proposes to analize, since the interdisciplinar perspective of Science of Religion, the relationships between habiliment and Black memories in the angola candomblé “terreiro” (ground - where candomblé's community reunite) Redandá, located in Embu-Guaçu, municipality of the Metropolitan Area of São Paulo. In dialogue with the Post-Colonial Theory, we consider orality and gestuality fundamental aspects for the afro-diasporic experience to be comprehended. Thus, assuming that habiliment, as extension of corporeality and black religiosity expression, is constitutive of the religious experience developed by Redandá's adepts. The vestment allows to think a correlation between body and the sacred, relating africanities and black aesthetics. By prioritizing the aesthetic dimension, the basic assumption is that the clothes as well as body adornments, exceed the function of covering and protecting the body and also extrapolate the meaning of beauty, exerting important functions that auxiliate to comprehend the liturgical dimension and ritual of the “terreiro” and the livingness of the community being studied